Effects of preconceptional weekly micronutrient supplements on maternal and child anemia during the first 2 years of life - Nguyen, Phuong Hong; Young, Melissa F.; Gonzalez-Casanova, Ines; Truong, Truong V.; Nguyen, Son; Martorell, Reynaldo; Ramakrishnan, Usha (Wiley, 2017)
Anemia remains a major public health problem especially during the first 1000 days of life. Prenatal supplementation with multiple micronutrients (MM) and iron and folic acid (IFA) has been suggested as a potential intervention to reduce anemia in young children but little is known about the benefits of preconception micronutrient interventions. This study evaluates the impact of preconception weekly MM or IFA supplementation on maternal and child anemia during the first 2 years of age compared to folic acid (FA) alone.